(untitled) (Ukrainian Journal of Ophthalmology, 2023)
Purpose: to determine the consistency of HVID/WTW measurements on 5 devices, and their correspondence to the distance from angle to angle (ATA). Methods The relevant information on 30 right eyes was obtained from 30 volunteers. A prospective study was conducted using Wavelight Topolayzer Vario (Alcon), IOL Master 700 (Zeiss), OA2000 (Tomey), AS-OCT Casia 2 (Tomey), Zeiss Atlas 9000 (Carl Zeiss) instruments. Agreement between the measurement s made by these devices in the HVID/WTW was analyzed, and the HVID/WTW scores of each device were compared with ATA scores. Results The average values ​ ​ of HVID/WTW in Wavelight Topolayzer Vario, IOL Master 700, OA2000, Zeiss Atlas 9000 devices were 11.73 ± 0.33 mm, 12.01 ± 0.34 mm, 12.01 ± 0.27 mm, and 12.2 ± 0.37 mm, respectively. The mean ATA was 11.68 mm on the AS-OCT Casia2 device. The smallest difference in ATA and HVID/WTW was observed on the Wavelight Topolyzer Vario instrument which averaged 0.05±0.102mm 95% LoA (-0.41 to 0.32) (p < 0.05). The largest difference was observed between AS-OCT Casia 2 and Atlas 9000 which averaged 0.52±0.234mm 95% LoA (from-1.21 to 0.17) (p < 0.05). Conclusion Our study found that the results of measurements of HVID/WTW on the Wavelight Topolayzer Vario device are optimal when compared with ATA.